Selamat Natal dalam al-Qur’an dan Hadits - Asmuki , Asmuki (Al-Insyiroh: Jurnal Studi Keislaman, 2018)
In this article, we will try to discuss verses and hadith related to other religious holidays. The discussion of Muslim holiday greetings to other religious followers will begin with a search for the Qur'anic verses used by Muslim thinkers in their arguments, then interpretive reviews that have been carried out by commentators, then the study of those verses will be completed with the hadiths and the content of their meaning which has ties and contact with the intended verses. Finally, the two types of texts will be searched for each of them according to the phenomenon of landing verse (asbab al-nuzul) and hadith (asbab al-wurud).